Effects of (−)-epicatechin on frontal cortex DAPC and dysbindin of the mdx mice - Estrada Mena, Francisco Javier; Rodríguez, Alonso; Mendoza-Lorenzo, Patricia; Neri-Gómez, Teresa; Rodríguez, Sergio; Ordonez-Razo, Rosa; Ceballos, Guillermo; Villarreal, Francisco; Ramírez-Sánchez, Israel (My University, 2017)
Introduction: Multiple components of the dystrophin-associated protein complex (DAPC) are expressed in numerous tissues including the brain. Members of the DAPC and dysbindin are abnormally expressed in the brain of Duchenne Muscular Dystrophy (DMD) patients, which has been associated with cognitive impairments. However, little is known about the expression pattern of individual members of the DAPC in animal models of DMD and their relationship with dysbindin. Methods: Ten mdx mice were randomly allocated into a control and intervention group [(−)-epicatechin (Epi) 1 mg/kg/day for four weeks] and results compared to a wild-type mice. After sacrifice, brain pre-frontal cortices were collected for Western blotting and immunoprecipitation assays, and sagittal sections processed for immunohistochemistry.
Effects of (−)-epicatechin on frontal cortex DAPC and dysbindin of the mdx mice